Prevalência e fatores associados à violência doméstica : estudo em uma maternidade de alto risco - Fiorotti, Karina Fardin (2016)
Introduction: Domestic Violence is a phenomenon that persists in many places around the world, in a silent and trivialized way, and in genearl it has as the main perpetrator someone who is inside the social circle of the victims. This phenomenon may affect women in their several different life cicles. Objective: To describe the prevalence of the different domestic violence types between puerperal women in a high risk maternity; to examine the association of these occurences with the demographic, socio-economic and reproductive variables. Method: This is an epidemiological, analytical, observational study of the transversal type. The study included 302 women with at least 24 hours after birth, and who were hospitalized at the maternity of the University Hospital Cassiano Antonio Moraes in the monthe of June to September of 2016 were approached. The data was collected through an interview with registration on a form. A form for socio-economic, demographic and reproductive data, as well as the AAS - Abuse Assessment Screen, for the screening of domestic violence were used. Results: Among the interviewees, 43% of the puerperal women reported having experienced maltreatment situations throughout their lives, 7.6% were victims of physical violence in the 12 months prior to the interview, and 4.6% were in a physical violence situations during pregnancy. There was a statistical association even after regression between the interviewees' endpoint maltreatment throughout the life and the variables age, religion and number of pregnancies. In the same way, having experienced physical violence in the previous year, and physical violence during pregnancy were strongly associated to the marital status of the puerperal woman. Products: In regard to the products, the folder was elaborated with the instructions of the women concerning the types of violence and the support networks the maternity's data collection instrument with questions about domestic violence was broeadened. Conclusion: This study reasserts that violence constitutes an ever present phenomenon in the life of women, including during pregnancy, and it has shown an association to the victim's demographic and obstetric conditions. Besides that, it is understood that a strategy to face violence is the use of instruments on the part of the healthcare service, in order to allow for the identification of violence and hence promote a more qualified care to the victims, as well as the process of education about health needs to be a part of the professionals' activities, with instructions to the patients about the phenomenon of violence against women.